Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/molecules26020494
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Glycosides in Brassica Species Respond to UV-B Depending on Exposure Time and Adaptation Time

Abstract: Recently, there have been efforts to use ultraviolet-B radiation (UV-B) as a biotechnological tool in greenhouses. Leafy Brassica species are mainly considered for their ability to synthesize glucosinolates and are valued as baby salads. They also have a remarkable concentration of chemically diverse flavonoid glycosides. In this study, the effect of short-term UV-B radiation at the end of the production cycle was investigated without affecting plant growth. The aim was to verify which exposure and adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
(87 reference statements)
4
14
0
Order By: Relevance
“…Using a complementary approach, Yi et al, (2019) performed de novo transcriptome sequencing in both green and white types of a commercial variety (Atlas) and found significant differences between the two asparagus types in that 21% of the genes involved in the biosynthesis of the flavonoid rutin were upregulated in green and 4% of the genes involved in the biosynthesis of the saponin protodioscin were upregulated in white asparagus [ 41 ]. These results followed and confirmed other studies, which focused on quantifying these two compounds in green and white asparagus, as well as other flavonoids and saponins [ 22 , 32 , 39 , 42 , 43 ], suggesting that indeed metabolic pathways are differently active in green and white asparagus shoots.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Using a complementary approach, Yi et al, (2019) performed de novo transcriptome sequencing in both green and white types of a commercial variety (Atlas) and found significant differences between the two asparagus types in that 21% of the genes involved in the biosynthesis of the flavonoid rutin were upregulated in green and 4% of the genes involved in the biosynthesis of the saponin protodioscin were upregulated in white asparagus [ 41 ]. These results followed and confirmed other studies, which focused on quantifying these two compounds in green and white asparagus, as well as other flavonoids and saponins [ 22 , 32 , 39 , 42 , 43 ], suggesting that indeed metabolic pathways are differently active in green and white asparagus shoots.…”
Section: Discussionsupporting
confidence: 89%
“…For example, higher saponin levels are typical of asparagus roots [ 18 , 38 ] as well as white shoots compared to green ones ( Table 1 ). In this regard, David and Hofmann (2014) [ 39 ] and Lee et al, (2010) [ 22 ] found higher concentrations of saponins in the stem sections closer to the crown/roots of white asparagus, compared to the young asparagus tips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported an enhanced effect of UV light or low temperature on the biosynthesis of quercetins, condensed tannins and flavonoid glycosides in plants [ 81 , 84 , 85 ]. These substances have a variety of resilient biological activities against UV radiation, low temperature or drought [ 21 , 25 , 26 ], and our results are consistent with these previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated total phenolic content was observed in highbush blueberry leaves ( Vaccinium corymbosum L. cv. Bluegold) exposed to UV-B for 24 h. In addition, Neugart and Bumke-Vogt (2021) investigated the effects on major genes expression of the phenylpropanoid pathway, contents of the flavonoid groups, and hydroxycinnamic acid derivatives after short-term UV-B irradiation and before the harvest of various Brassica species ( B. rapa, B. nigra, B. oleracea, B. juncea, B. napus , and B. carinata ). The response during the acclimation period after the UV-B irradiation (2 and 24 h) was investigated, but the response immediately after the UV-B irradiation was not confirmed.…”
Section: Introductionmentioning
confidence: 99%